2021
DOI: 10.1073/pnas.2101115118
|View full text |Cite
|
Sign up to set email alerts
|

Clock proteins and training modify exercise capacity in a daytime-dependent manner

Abstract: Exercise and circadian biology are closely intertwined with physiology and metabolism, yet the functional interaction between circadian clocks and exercise capacity is only partially characterized. Here, we tested different clock mutant mouse models to examine the effect of the circadian clock and clock proteins, namely PERIODs and BMAL1, on exercise capacity. We found that daytime variance in endurance exercise capacity is circadian clock controlled. Unlike wild-type mice, which outperform in the late compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 67 publications
2
30
1
Order By: Relevance
“…Chronobiology and circadian rhythms have gained accumulating interest in healthcare; specifically their interactions with other processes that govern metabolism and whole-body physiology ( Burki, 2017 ). Exercise biology, including physical activity (PA) intensity, similarly explains mechanisms relating to overall health and metabolism ( Adamovich et al, 2021 ), thus, both PA and circadian rhythms are of interest from a public health perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Chronobiology and circadian rhythms have gained accumulating interest in healthcare; specifically their interactions with other processes that govern metabolism and whole-body physiology ( Burki, 2017 ). Exercise biology, including physical activity (PA) intensity, similarly explains mechanisms relating to overall health and metabolism ( Adamovich et al, 2021 ), thus, both PA and circadian rhythms are of interest from a public health perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Type I fibers have a lower maximum sarcoplasmic reticulum Ca2 + -ATPase activity and, therefore, female skeletal muscle metabolism is more suited to resynthesizing ATP from oxidative phosphorylation during exercise [ 64 ]. Notably, another study recently reported that female mice have greater exercise capacity at ZT22 than they have at ZT14, using a different exercise test that preferentially measures endurance exercise capacity as revealed by depletion of circulating glucose [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that voluntary running wheel activity consolidated in the early nighttime active phase led to increased running endurance regardless of the time of day, but enhanced maximal running speed only later in the night. Several circadian clock components influence muscle function and/or exercise capacities, including CRYs, PERs, FBXL21, and BMAL1 [ 6 , 10 , [14] , [15] , [16] , [17] , 28 , 65 , [72] , [73] , [74] , [75] , [76] ]. Notably, CRYs are phosphorylated by AMPK [ 77 ] and repress the transcription factors HIF1α [ 32 , 33 ] and PPARδ [ 17 ], each of which are established effectors of exercise-induced remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Additional candidate genes were identified in the muscle of unselected control mice controlled by exercise (Clock, Ncam1, Fgfr4, and Hbegf). For these candidates, specific roles have been suggested with respect to metabolic adaptation [ 41 ], muscle innervation [ 42 ], training responses [ 43 ], or muscle cell differentiation [ 44 ]. It is possible that decades of selection under avoidance of inbreeding have enriched multiple mechanisms related to superior running performance in DUhTP mice, which might also warrant separate studies in the future.…”
Section: Discussionmentioning
confidence: 99%